Can Environmental Ethics 'Solve' Environmental Problems and Save the World? Yes, but First We Must Recognise the Essential Normative Nature of Environmental Problems. (1st November 2003) - Kassiola, Joel J.
What is the nature of environmental problems? This article attempts to illuminate this question by exploring the relationship between environmental ethics, environmental problems and their solution. It does this by examining and criticising the argument contained in a recent issue of Environmental Values asserting that environmental ethics does not have a role to play in solving environmental problems. The major point made in this rebuttal article is that environmental problems are essentially normative in nature. Therefore, normative discourse, and environmental ethics in particular, do have a crucial role to play in environmental thought and action. The discussion concludes with the judgment that a failure to recognise this essential contribution of normative discourse to environmentalism by committing to a conservative empirical reductionism of environmental problems is detrimental to the necessary ethical and social change required to save the world.